2017
DOI: 10.1016/j.jtho.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Improved Overall Survival with Aggressive Primary Tumor Radiotherapy for Patients with Metastatic Esophageal Cancer

Abstract: Definitive dose, but not conventional palliative dose, PTDRT is associated with improved overall survival in metastatic esophageal cancer, suggesting that local control may be important to prognosis. These findings support integrating PTDRT into future clinical trials aimed at refining personalized treatment for patients with metastatic esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Several retrospective and prospective studies have suggested that palliative radiotherapy could improve survival in metastatic EC. 27 29 In addition, several recent retrospective studies found that resection of primary tumors may be considered for a select group of patients with stage IV EC who achieve a favorable response to systemic chemotherapy. 18 , 19 , 30 Our previous study of the SEER database also found that surgery and preoperative radiotherapy were associated with better survival in metastatic EC.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and prospective studies have suggested that palliative radiotherapy could improve survival in metastatic EC. 27 29 In addition, several recent retrospective studies found that resection of primary tumors may be considered for a select group of patients with stage IV EC who achieve a favorable response to systemic chemotherapy. 18 , 19 , 30 Our previous study of the SEER database also found that surgery and preoperative radiotherapy were associated with better survival in metastatic EC.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that eradication of the primary tumor can improve long-term outcomes in the metastatic setting was first demonstrated prospectively in patients with renal cell carcinoma. 7,8 Since then, a large body of retrospective data studying esophageal, 6 bladder, 9 and prostate cancers 10 has demonstrated an association between definitive treatment of the primary site and improved OS. Such studies in cervical cancer are extremely limited and primarily focus on patients with recurrent metastatic disease after prior definitive treatment.…”
Section: E382mentioning
confidence: 99%
“…Despite these limitations, our findings are mechanistically plausible and concordant with results demonstrated in similar studies of other malignancies. [6][7][8][9][10]…”
Section: E382mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Depypere et al 9 recently reported patients with esophageal cancer and solitary solid organ metastases achieved good median overall survival of 54 months after surgery, which was superior to chemotherapy alone. Guttmann et al found definitive dose radiotherapy was associated with improved survival compared to conventional palliative dose radiotherapy based on analysis of 12683 patients with esophageal cancer 15 . These studies indicate that-similarly to brain metastases-patients with solitary solid organ metastases may achieve better treatment outcomes after definitive local treatment of recurrent lesions.…”
Section: Discussionmentioning
confidence: 99%